2021
DOI: 10.1002/mop.33056
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution passive imaging by electromagnetic vortex beams

Abstract: A new scheme to achieve high resolution in passive millimeter wave imaging (PMMWI) using electromagnetic (EM) vortex beams is proposed in this article. The spatial resolution of the traditional PMMWI system based on the mechanically or electronically controlled scanning scheme is mainly limited by the beam width of the receiver. However, it is not practical to fabricate an antenna that is too large, another possible way to improve the resolution is to increase the sampling points but will increase the imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Guo S. et al proposed a mechanically controlled imaging high-resolution imaging method based on electromagnetic vortex beam imaging in order to improve the high resolution of the imaging. The results showed that the method can reduce the number of orbital angular momentum modes and improve the imaging resolution [8]. Yuan H. et al proposed a high-resolution imaging method based on a uniform circular array antenna for the problem of low quality of uniform circular array imaging.…”
Section: Related Workmentioning
confidence: 99%
“…Guo S. et al proposed a mechanically controlled imaging high-resolution imaging method based on electromagnetic vortex beam imaging in order to improve the high resolution of the imaging. The results showed that the method can reduce the number of orbital angular momentum modes and improve the imaging resolution [8]. Yuan H. et al proposed a high-resolution imaging method based on a uniform circular array antenna for the problem of low quality of uniform circular array imaging.…”
Section: Related Workmentioning
confidence: 99%
“…They open up numerous new and exciting possibilities in fiber optical communication, 8,9 wireless optical communication, 10,11 optical manipulation 12 . In recent years, partially coherent vortex beam also becomes a research hotspot in the academic community 13–17 . Compared with fully coherent vortex beams, partially coherent vortex beams have unique properties in physics and optics.…”
Section: Introductionmentioning
confidence: 99%
“…12 In recent years, partially coherent vortex beam also becomes a research hotspot in the academic community. [13][14][15][16][17] Compared with fully coherent vortex beams, partially coherent vortex beams have unique properties in physics and optics. Especially the joint regulation of its coherence and topological charge will lead to new properties, such as coherent singularities, 17 polarization state conversion, 18 and beam shaping.…”
Section: Introductionmentioning
confidence: 99%